Development Of An Android-Based Electronic Instrument Using Ispring Suite For Testing The Concept Understanding Ability Of Grade 7 Flat Shapes - Caterien Elsa Carolien; Elwan Stiadi; Tria Utari (International Journal of Innovation and Education Research, 2026)
This research was motivated by the low level of students' mathematical concept understanding skills and the suboptimal use of technology in learning evaluations at SMPN 07 Bengkulu City. This study aimed to develop an Android-based electronic instrument using iSpring Suite for testing the concept understanding ability of seventh-grade flat shape material that was logically valid, had good item feasibility, and was practical to use. This research was a development study (Research and Development) employing the ADDIE model, which included the stages of analysis, design, development, implementation, and evaluation. The research subjects were seventh-grade students of SMPN 07 Bengkulu City, consisting of 28 students for the first field test and 28 students for the second field test. The research instruments included item validation sheets, Android application validation sheets, practicality sheets, and electronic test instruments. Data analysis techniques used the Aiken index for logical validity, point-biserial correlation for empirical validity, KR-20 for reliability, as well as analysis of difficulty index, discriminatory power, and distractors. The results showed that all 20 items and the Android application were declared logically valid with Aiken's V indices ranging from 0.87 to 0.92 (high category). The empirical test results indicated that all 20 items were valid and reliable with a KR-20 value of 0.853 (very high category), and met the criteria for difficulty index, discriminatory power, and distractors. The practicality test using the USE Questionnaire obtained a score of 86.67% with a very practical category. This research concluded that the developed Android-based iSpring Suite electronic instrument met the criteria of being valid, feasible, and practical for use as a test of flat shape concept understanding skills in junior high school.